Determining meat freshness using electrochemistry: Are we ready for the fast and furious?. (April 2019) - Johnson, Joel; Atkin, Dianne; Lee, Kyunghee; Sell, Marie; Chandra, Shaneel
Abstract: Electrochemistry is providing a variety of sensors at an extremely rapid pace. Many of these sensors offer powerful attributes like a multitude of platforms like voltammetry, impedimetry, amperometry and conductometry, as well as sensor-related gains like high sensitivity, selectivity and low cost. It is natural that their applications to food, especially meat freshness determination, are also increasing. Novel methods for rapidly assessing meat freshness are vital for meeting the increasing worldwide demand for meat products. Therefore, we present a short and succinct review of the most promising electrochemical sensor types, including those based on conductive polymers, nanocomposites and metal nanoparticles. From the wide range of sensors that have been designed to detect microbial pathogens and chemical degradation, we have covered a basic snapshot to yield an impression of recent gains in the research genre of meat freshness.